1992
DOI: 10.1017/s0317167100042256
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Temporal Bone With Exsanguination: Pathology and Mechanism

Abstract: ABSTRACT:Eight cases of basal skull fracture with transverse fracture of the petrous temporal bone with medial extension to the internal carotid artery and lateral extension of the structures of the middle ear are described. Injuries in all cases were due to major blunt impact to the head usually occurring in a motor vehicle accident. General autopsy revealed major blood loss without any obvious external or internal site of hemorrhage suggesting that exsanguination was a complication of the head injury. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 6 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Of the expected stereotypical injury patterns examined, only bleeding from the ears was found to be predictive of internal injury (base of skull fracture). This bleeding may result from a displaced base of skull fracture where a conduit between the cranial cavity and the middle ear is opened to allow egress for intracranial bleeding (Pollanen et al, 1992). Bleeding from both ears was highly predictive (95%) of a basal skull fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Of the expected stereotypical injury patterns examined, only bleeding from the ears was found to be predictive of internal injury (base of skull fracture). This bleeding may result from a displaced base of skull fracture where a conduit between the cranial cavity and the middle ear is opened to allow egress for intracranial bleeding (Pollanen et al, 1992). Bleeding from both ears was highly predictive (95%) of a basal skull fracture.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,12,23,31 Pollanen et al evaluated a series of 8 fatal basilar skull fractures and found that fractures of the petrous portion of temporal bones will often involve laceration of the internal carotid arteries, leading to massive hemorrhage. 21 These fractures can involve the middle ear as well and create a carotid-middle ear fistula leading to rapid exsanguination. 21,30 The grave prognosis of these high-velocity sports injuries from atlantooccipital dissociation, fatal vascular injuries, and concurrent basilar skull ring fractures necessitated further investigation into prevention and safety.…”
Section: The Hans Devicementioning
confidence: 99%
“…21 These fractures can involve the middle ear as well and create a carotid-middle ear fistula leading to rapid exsanguination. 21,30 The grave prognosis of these high-velocity sports injuries from atlantooccipital dissociation, fatal vascular injuries, and concurrent basilar skull ring fractures necessitated further investigation into prevention and safety. Trammell and Hubbard explored medical and technical outcomes of the HANS device in Championship Auto Racing Team (CART) series racing.…”
Section: The Hans Devicementioning
confidence: 99%